Mucocutaneous lymphonodular syndrome (Kawasaki) in a three-year-old child (the clinical case description) - A. P. Pakhomov; E. V. Saveleva; I. V. Zorin; R. A. Gumirova (Лечащий Врач)
Background. Kawasaki syndrome (mucocutaneous lymphonodular syndrome) is an acute systemic disease with damage to small and medium arteries and the development of destructive-proliferative vasculitis, which occurs mainly in children under five years of age. Its etiology and pathogenesis are still unclear, but it is believed that the disease is a manifestation of a combination of complex interactions of genetic factors, infections and immunity. Due to the peculiarities of the clinical picture (multiple organ damage and complexity of diagnosis), the disease occupies a special place in the work of a practicing pediatrician.Objective. The purpose of the work is to present the features of the course of a case of Kawasaki syndrome in a 3-year-old child based on clinical observation.Materials and methods. Analysis of the medical record of an inpatient f.003/u, clinical and genealogical method, functional research methods (ultrasound of the abdominal organs, lymph nodes, electrocardiography, heart ultrasound), clinical and biochemical analysis of blood and urine. A literature review based on the results of a search of literary sources in the eLIBRARY.RU, PubMed databases. The analysis included literature reviews, scientific articles, monographs, and clinical studies.Conclusion. The case we presented confirms the need for pediatricians to be alert to children with the following clinical manifestations: fever, conjunctival injection, changes in the mucous membranes (dry, cracked lips; raspberry tongue, hyperemia of the lips and oropharynx), rash (polymorphic – maculopapular, urticarial, scarlet fever-like, or even morbilliform without vesicles or crusts). Kawasaki syndrome can occur under the "mask" of an acute respiratory infection, endocarditis, and a number of rheumatological diseases. Children who have catarrhal (catarrhal symptoms of the mucous membrane of the oropharynx, conjunctivitis), articular, skin syndromes in combination with fever, as well as cervical lymphadenitis, must undergo heart ultrasound.